Cocos, Contagion and Systemic Risk - Stephanie Chan; Sweder van Wijnbergen (Tinbergen Institute, 2014)
CoCos (contingent convertible capital) are designed to convert from debt to equity when banks need it most. Using a Diamond-Dybvig model cast in a global games framework, we show that while the CoCo conversion of the issuing bank may bring the bank back into compliance with capital requirements, it will nevertheless raise the probability of the bank being run, because conversion is a negative signal to depositors about asset quality. Moreover, conversion imposes a negative externality on other banks in the system in the likely case of correlated asset returns, so bank runs elsewhere in the banking system become more probable too and systemic risk will actually go up after conversion. CoCos thus lead to a direct conflict between micro- and macroprudential objectives. We also highlight that ex ante incentives to raise capital to stave off conversion depend critically on CoCo design. In many currently popular CoCo designs, wealth transfers after conversion actually flow from debt holders to equity holders, destroying the latters incentives to provide additional capital in times of stress. Finally the link between CoCo conversion and systemic risk highlights the tradeoffs that a regulator faces in deciding to convert CoCos, providing a possible explanation of regulatory forbearance.
Keywords: G01; G21; G32; 330; Contingent Convertible Capital; Contagion; Systemic Risk; Bank Runs; Global Games